PELATIHAN PEMBUATAN “MIKUNG” (MIE KANGKUNG) UNTUK PETANI KANGKUNG DI KECAMATAN LINGSAR LOMBOK BARAT - Citra Ayu Dewi; Yeti Kurniasih; Diah Lukitasari; Abdul Sakban (Jurnal Lentera Widya, 2021)
The main problems and obstacles faced by water spinach farmers in the Lingsar area are the limited knowledge of farmers in recognizing vegetable market behavior so that farmers rely heavily on traders or collectors in the Lingsar area, inefficient marketing, and skills to develop kale vegetable products into products. Processed products that have a longer shelf life, have economic value, and have quality and properties as food supplements are not yet known by the farming community in the Lingsar area, even though the ingredients of kale are a source of vegetable protein and fiber which are beneficial for body metabolism. This service activity aims to increase understanding of kale farmers in the processed products of kale into kale noodles. This service activity has been carried out for 1 month. The methods of this service include: delivery of material, direct training and practice. Delivery of material about the introduction of chemical composition, nutritional content and functional food elements (added value) in kale. Training and hands-on practice in making kale noodles as an innovative product of kale vegetables to train the skills of kale farmers in Lingsar District, West Lombok Regency. Based on the evaluation results after the training, it showed that most of the participants gained new understanding and knowledge about making noodles, especially the addition of water spinach as an added ingredient in vegetable protein. So, it can be concluded that training in making kale noodles can increase understanding of kale farmers in processing kale products.